2020
DOI: 10.1111/ppl.13143
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between melatonin and nitric oxide in plant development and stress responses

Abstract: Melatonin is widely involved in plant growth and stress responses as a master regulator. Melatonin treatment alters the levels of endogenous nitric oxide (NO) and NO affects endogenous melatonin content. Melatonin and NO may induce various plant physiological behavior through interaction mechanism. However, the interactions between melatonin and NO in plants are largely unknown. The review presented the metabolism of endogenous melatonin and NO and their relationship in plants. The interactions between melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…For example, exogenous application of melatonin increased NO production in alfalfa [110] and Arabidopsis [111]. It is believed that the interaction of NO and melatonin is through a cGMP-dependent pathway [112]. Although melatonin has been shown to positively regulate NOS-mediated NO biosynthesis in neuronal cells [113], as well as inducing mitochondrial NOS mRNA expression and protein synthesis [114], this molecule may suppress NOS activity during nitrosative stress [110].…”
Section: Synergistic Relationship Of No With Other Signaling Moleculesmentioning
confidence: 99%
“…For example, exogenous application of melatonin increased NO production in alfalfa [110] and Arabidopsis [111]. It is believed that the interaction of NO and melatonin is through a cGMP-dependent pathway [112]. Although melatonin has been shown to positively regulate NOS-mediated NO biosynthesis in neuronal cells [113], as well as inducing mitochondrial NOS mRNA expression and protein synthesis [114], this molecule may suppress NOS activity during nitrosative stress [110].…”
Section: Synergistic Relationship Of No With Other Signaling Moleculesmentioning
confidence: 99%
“…Moreover, melatonin shows interaction with different phytohormones and signalling molecules [ 17 , 21 ]. He and He [ 22 ] have reported melatonin and nitric oxide (NO) may actuate different plant physiological responses through their association under both normal or stress conditions and hydrogen sulfide (H 2 S) communicates with ROS and NO influencing the two ROS and responsive nitrogen species (RNS) uptake [ 23 , 24 ]. Mukherjee and Bhatla [ 25 ] found that both H 2 S and melatonin ameliorated salt stress mediated decrease in tomato growth and exogenous melatonin modulated early H 2 S signalling.…”
Section: Introductionmentioning
confidence: 99%
“…MET acts together with NO in plant growth and mediates plant abiotic stress tolerance through the improvement of the antioxidant system [79] (Figure 4).…”
Section: No-plant Mediated Stress Response and Its Relationship With Metmentioning
confidence: 99%